Histopathological and functional changes in the testicles of albino rats experimentally infected with Arcobacter butzleri - ADESIJI, Yemisi Olukemi; EMIKPE, Benjamin Obukowho; OPALEKUNDE, Ahmed Bayo (Acta medica Lituanica, 2011)
Background. Arcobacter is an emerging zoonotic enteropathogen associated with spontaneous abortion, diarrhea and mastitis in domestic animals. Materials and methods. Thirty male pathogen-free albino rats were infected with a single challenge of Arcobacter butzleri (108 cfu/ml) isolated from the stool of healthy pigs with the aim of investigating the effects of A. butzleri on rat testicular histology and spermatogenesis. Results. In previously healthy male albino rats, A. butzleri caused testicular degeneration associated with reduced sperm count and motility. Conclusions. The result of this study suggests that A. butzleri produces testicular degeneration and the associated disruption of spermatogenesis in albino rats; hence, its infertility potential in livestock industry and its economic importance should be further investigated. Keywords: Arcobacter butzleri, testicular degeneration, infertility,pathogenicity, sperm count, albino rats